The United States Government and the Greek War of Independence - Theodosios Karvounarakis (European Journal of American Studies)
While the Greek War of Independence enjoyed remarkable support among the United States public, the Government of the United States was very cautious in its reaction. Reluctant to assume onerous international obligations and fearful of alienating the European Great Powers, it limited itself to moral support and some gestures of good will, involving minimum risk.